EFFECT OF SEASON ON FREQUENCY OF EJACULATE DISCARD IN HF CROSSBRED BULLS - SHRIVATAVA, NOOPUR; AWASTHl, M K; NAIR, A K; TIWARl, R P; POYAM, M R; MISHRA, G K (The Indian Journal of Animal Reproduction, 2023)
The discard frequency of semen ejaculate in six HF crossbred bulls was studied for five calendar years. Data were grouped based on season viz. summer (March to June), rainy (July to October) and winter (November to February) season. A total of 215 (9.00%) ejaculates were discarded out of 2388 semen collections during five years period. Ejaculate discard frequency was 9.87 per cent (55/557) during summer season, while the corresponding values for rainy and winter season were 9.79 per cent (76/776) and 7.96 per cent (84/1055), respectively. There was non-significant difference in ejaculate discard frequency among three seasons. The semen ejaculates were discarded based on lower volume, poor sperm concentration, poor initial motility and post-thaw motility. The highest frequency of discard (47.90%) was recorded for poor sperm concentration followed by poor initial motility (26.04%), poor post-thaw motility (23.72%) and lower volume (2.32%) during summer season. Similar trend was observed during rainy and winter season. Although poor concentration was the main factor for ejaculate discard during winter season; the frequency of poor initial and post-thaw motility was almost similar.